Competitiveness Strategy of Traditional Market: Case Study in Panorama Lembang, West Bandung, Indonesia - Purwanti, Yanti; Heru, Bambang; Jamaludin, Maun (LifeSciFi, 2022)
This research aims to describe the strategy that can be formulated as physical improvement and improving the function and attractiveness of the Panorama Lembang Bandung traditional market. The main consideration in this qualitative study is to highlight the capability of the traditional market to create something distinctive and unique but a level of comfort, security, and cleanliness. This research was conducted in West Bandung Regency. The location selection was purposively made because Bandung is one of the regions of West Java. The data used in this study are primary and secondary in qualitative technique. The results highlight the encouragement for central and regional governments to synergize and support the empowerment of the Panorama traditional market. The strategies are by enforcing and complying with the regulations that have been made. The suggestion that can be put forward is that the traditional market should be able to create and cultivate a clean, safe, orderly, and more attractive market atmosphere. With a focus on consumers, through efforts to understand consumer needs, wants, and expectations, the best service to consumers is the key to winning an increasingly fierce competition.